A Low‐Temperature Carbon Encapsulation Strategy for Stable and Poisoning‐Tolerant Electrocatalysts. Issue 11 (14th September 2021) - Hu, Yezhou; Zhang, Jujia; Shen, Tao; Lu, Yun; Chen, Ke; Tu, Zhengkai; Lu, Shanfu; Wang, Deli
Abstract: Carbon encapsulation is an effective strategy for enhancing the durability of Pt‐based electrocatalysts for the oxygen reduction reaction (ORR). However, high‐temperature treatment is not only energy‐intensive but also unavoidably leads to possible aggregation. Herein, a low‐temperature polymeric carbon encapsulation strategy (≈150 °C) is reported to encase Pt nanoparticles in thin and amorphous carbonaceous layers. Benefiting from the physical confinement effect and enhanced antioxidant property induced by the surface carbon species, significantly improved stabilities can be achieved for polymeric carbon species encapsulated Pt nanoparticles (Pt@C/C). Particularly, a better antipoisoning capability toward CO, SO x, and PO x is observed in the case of Pt@C/C. To minimize the thickness of the catalyst layer and reduce the mass transfer resistance, the high mass loading Pt@C/C (40 wt%) is prepared and applied to high‐temperature polymer electrolyte membrane fuel cells (HT‐PEMFCs). At 160 °C, a peak power density of 662 mW cm −2 is achieved with 40% Pt@C/C cathode in H2 –O2 HT‐PEMFCs, which is superior to that with 40% Pt/C cathode. The facile strategy provides guidance for the synthesis of highly durable carbon encapsulated noble metal electrocatalysts toward ORR. Abstract : Carbon‐encased Pt nanoparticles (Pt@C/C) are prepared via a low‐temperature decomposition strategy. Enhanced durability and antipoisoning capability are achieved due to the in situ formed protective "carbon armor." To minimize mass transfer resistance, the high Pt loading catalyst (40% Pt@C/C) is obtained and a peak power density of 662 mW cm −2 is achieved in HT‐PEMFCs at 160 °C.